Determinan Kejadian Stunting di Desa Ngampelrejo Kecamatan Jombang Kabupaten Jember Tahun 2023 - Ayu Binti Mutammimah Ayu (JURNAL TAMPIASIH, 2024)
Stunting can be interpreted as a toddler who has a body size that is shorter than the standard age. The incidence of stunting can be influenced by several factors including nutritional intake, exclusive breastfeeding and environmental sanitation. The purpose of this study was to determine the determinants of stunting in Ngampelrejo village in 2023. This study used a quantitative design with a cross sectional approach. The sample in this study were 180 toddlers aged 0-59 months in Ngampelrejo village, Jember. The sampling technique used random sampling. The data used were primary data, namely observation sheet data on height measurements and the age of the child and a questionnaire about a diet high in protein, calcium and zinc. Data were analyzed using SPSS Version 22 with the chi square test at a significance level of α,0,05. The results showed there is a correlation between nutrient intake and environmental sanitation with the incidence of stunting in toddlers in Ngampelrejo village, Jombang, Jember. There is no correlation between exclusive breastfeeding and the incidence of stunting in toddlers in Ngampelrejo village, Jombang, Jember. This reason, special attention is needed from policy makers for interventions focused on maternal and child health to reduce stunting by raising awareness of mothers and families the importance of exclusive breastfeeding, nutritional intake for children through counseling and monitoring, still education for the public, especially those who have babies. and toddlers regarding environmental sanitation through counseling. Keywords: Nutrient, intake, exclusive breastfeeding, environmental sanitation, stunting